Cycle helmet ownership and use; a cluster randomised controlled trial in primary school children in deprived areas. Issue 4 (19th March 2004) - Kendrick, D; Royal, S
Abstract : Aims: To assess the effectiveness of two different educational interventions plus free cycle helmets, in increasing cycle helmet ownership and use. Methods: A cluster randomised controlled trial was carried out in 28 primary schools in deprived areas of Nottingham, involving 1213 year 5 schoolchildren (age 9 and 10). Children received either a helmet + educational pack (educational pack and order form for free cycle helmet) or a helmet + multifaceted intervention (educational pack, order form for free cycle helmet, school assembly, lesson devoted to cycle helmet education, and an invitation to a school based cycling event). Results: The helmet + educational pack was as effective as the helmet + multifaceted intervention in terms of helmet ownership (OR 1.51, 95% CI 0.50 to 4.58) and wearing (OR 0.98, 95% CI 0.57 to 1.68). Helmet ownership significantly increased from baseline with both interventions, and wearing significantly increased from baseline with the helmet + educational pack. The interventions reduced the inequality in helmet ownership between children residing in deprived and non-deprived areas that had been present prior to the study. Conclusions: An educational pack plus a form to order a free cycle helmet is an effective way of increasing bicycle helmet ownership and use and reduces inequalities in helmet ownership among children in deprived areas. Further work is needed to determine the length of the effect of such interventions.